Spill-point analysis and structural trapping capacity in saline aquifers using MRST-co2lab. (February 2015) - Møll Nilsen, Halvor; Lie, Knut-Andreas; Møyner, Olav; Andersen, Odd
Abstract: Geological carbon storage represents a substantial challenge for the subsurface geosciences. Knowledge of the subsurface can be captured in a quantitative form using computational methods developed within petroleum production. However, to provide good estimates of the likely outcomes over thousands of years, traditional 3D simulation methods should be combined with other techniques developed specifically to study large-scale, long-term migration problems, e.g., in basin modeling. A number of such methods have been developed as a separate module in the open-source Matlab Reservoir Simulation Toolbox (MRST). In this paper, we present a set of tools provided by this module, consisting of geometrical and percolation type methods for computing structural traps and spill paths below a sealing caprock. Using concepts from water management, these tools can be applied on large-scale aquifer models to quickly estimate potential for structural trapping, determine spill paths from potential injection points, suggest optimal injection locations, etc. We demonstrate this by a series of examples applied on publicly available datasets. The corresponding source code is provided along with the examples. Abstract : Highlights: We outline parts of an open-source toolbox for studying geological storage of CO2 . We present two classes of algorithms for computing structural traps and migration paths. We demonstrate how to compute storage capacity and identify good injection points using open data describing large aquifers in the North Sea.